The Effect of Aromatherapy on Reducing Anxiety in Pregnant Women with Emesis Gravidarum - Jumriani, Jumriani; Erniawati, Erniawati; Sumarni, Sumarni; Nurbaety, Nurbaety; Yayu, Putri; Adriani, Fitri (International Journal of Engineering, Science and Information Technology, 2025)
Beginning with ovulation and continuing through conception, nidation, implantation, and embryonic growth in the uterus, pregnancy is an ongoing process. Adapting mentally and physically to the effects of pregnancy hormones and the increased mechanical pressure from the growing uterus and other tissues is essential during pregnancy. The symptoms of morning sickness and vomiting, known as emesis gravidarum, typically manifest in the first trimester of pregnancy. Symptoms usually begin around six weeks following the last day of menstruation and continue for around ten weeks. However, they can sometimes extend into the second and third trimesters of pregnancy. This study, therefore, seeks to establish whether aromatherapy helps pregnant women who suffer from nausea and vomiting all through their nine months of gestation. The novelty of the method used in this study is that it tests a group of pregnant women both before and after the application of lemon aromatherapy. Researchers found that first-trimester pregnant women who used lemon aromatherapy had less anxiety and fewer symptoms of emesis gravidarum. Most people who tried the lemon acupressure said it helped them relax, even if the results of the statistical tests did not reveal a substantial reduction in anxiety. The limbic system, which controls our reactions to stress and other emotions, is activated by lemon aromatherapy via the olfactory pathway. Lemon essential oil contains bioactive components like citral and limonene, which have anxiolytic effects and can alleviate vomiting and nausea. This study aimed to find out whether aromatherapy helped pregnant women with emesis gravidarum feel less anxious. A quasi-experimental approach was employed with pre- and post-tests administered to one group. Findings from the study The Wilcoxon Signed Rank Test yielded a p-value of less than 0.025. It can be concluded that aromatherapy with lemon did not alleviate morning sickness anxiety in first-trimester pregnant ladies.